Contemporary Public Policy Issues in Industrial Relations - Hall, Noël (Relations industrielles / Industrial Relations, 1969)
The present system of collective bargaining is more an exercise in the use of coercive economic and political power by labour and management than a process of rational, logical argument and existing conciliation procedures have proven inadequate in reflecting the public interest in dispute settlement. What then is the impact of B.C. Bill 33 ?